Incidence of ventilator-associated pneumonia in Australasian intensive care units: use of a consensus-developed clinical surveillance checklist in a multisite prospective audit. Issue 10 (29th October 2015) - Elliott, Doug; Elliott, Rosalind; Burrell, Anthony; Harrigan, Peter; Murgo, Margherita; Rolls, Kaye; Sibbritt, David
Abstract : Objectives: With disagreements on diagnostic criteria for ventilator-associated pneumonia (VAP) hampering efforts to monitor incidence and implement preventative strategies, the study objectives were to develop a checklist for clinical surveillance of VAP, and conduct an audit in Australian/New Zealand intensive care units (ICUs) using the checklist. Setting: Online survey software was used for checklist development. The prospective audit using the checklist was conducted in 10 ICUs in Australia and New Zealand. Participants: Checklist development was conducted with members of a bi-national professional society for critical care physicians using a modified Delphi technique and survey. A 30-day audit of adult patients mechanically ventilated for >72 h. Primary and secondary outcome measures: Presence of items on the screening checklist; physician diagnosis of VAP, clinical characteristics, investigations, treatments and patient outcome. Results: A VAP checklist was developed with five items: decreasing gas exchange, sputum changes, chest X-ray infiltrates, inflammatory response, microbial growth. Of the 169 participants, 17% (n=29) demonstrated characteristics of VAP using the checklist. A similar proportion had an independent physician diagnosis (n=30), but in a different patient subset (only 17% of cases were identified by both methods). The VAP rate per 1000 mechanical ventilator days for the checklist and clinician diagnosis was 25.9 and 26.7, respectively. The item 'inflammatory response' was most associated with the first episode of physician-diagnosed VAP. Conclusions: VAP rates using the checklist and physician diagnosis were similar to ranges reported internationally and in Australia. Of note, different patients were identified with VAP by the checklist and physicians. While the checklist items may assist in identifying patients at risk of developing VAP, and demonstrates synergy with the recently developed Centers for Disease Control (CDC) guidelines, decision-making processes by physicians when diagnosing VAP requires further exploration.